Stakeholders Workshop on Farmer-Centric Digital Transformation of African Agriculture - Rupavatharam, Srikanth; Patil, Mukund; Gogumalla Pranuthi; Gumma, Murali Krishna; Kumar, Kishore G.; Kumar, Shalander; Jat, Mangi L. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
The science of Digital Agriculture has been gaining prominence with the advent of fast-paced technological progress that can enhance last-mile delivery to smallholder farmers. Digital Agriculture offers a wide range of technology solutions for farmers, including smart farming, precision agriculture, data-driven decision support, extension systems, channels for improved market access, and financial services (Townsend et al., 2019). Digital Agriculture can contribute to increased productivity and profitability of farms and strengthen access to diverse marketing channels and resilience to climate change. However, in most cases, Digital Agriculture technologies have not been adequately accessed by smallholder farmers, women, and youth (CTA, 2019). The United Nations Secretary General’s strategy on the use of digital technologies to accelerate the achievement of SDGs identifies food security as a critical area that will be profoundly disrupted by advances in Digital Agriculture (United Nations, 2018). The CGIAR Research Initiative on Digital Innovation has achieved substantial progress, generating 207 results, including 101 knowledge products, 43 innovations, 18 capacity-sharing activities, four policy change results, and four innovation use results. The CGIAR focused on developing innovations across five Work Packages in 2024, such as online platforms for research and learning, digital twin systems, an index for assessing digital inclusiveness, and remote sensing analytics – we are on track to achieve all End of Initiative outcome goals in 2024.